Performance analysis of "V"-type solar still with tilt wick and effect of wick coverage. Issue 1 (1st January 2017) - Suneesh, P.U.; Jayaprakash, R.; Kumar, Sanjay; Denkenberger, David
Abstract: Solar distillation has yet to achieve widespread acceptance due to various technical difficulties and maintenance requirements which might not be acceptable or feasible for local communities. Emphasis has now shifted on the assimilation of locally available materials and expertise for optimum output. Coimbatore and nearby areas in South India have cotton waste material because the textile industry has flourished over the past ten years. A new design of wick and the performance of the solar still are parametrically analyzed in this paper. A "V"-type solar still of 1.5 m 2 was constructed for experimental verification and data collection. The glass temperature, ambient air temperature and solar radiation were recorded during the sunny days. The effect of the tilt angle in the Coimbatore climatic conditions is also presented in this paper. The system was tested in two ways: (1) tilt basin fully covered by wick and, (2) tilt basin partially covered by the wick. Since the partial coverage of the wick yielded higher output and would be lower cost, this is the superior arrangement. The optimum tilt of the wick was found to be 25°. The system with tilt basin fully covered by wick produced distillate yield of 3, 365 ml (m 2 -day) whereas the system with tilt basin partially covered by wick produced distillate yield of 3, 640 ml (m 2 -day).